COMPARISON BETWEEN THE EFFECT OF AN ACUTE RESISTANCE EXERCISE SESSION IN SERIES METHOD WITH INTENSE AND LIGHT LOAD ON BLOOD PRESSURE AND DOUBLE PRODUCT (Fiep Bulletin - online, 2011)
Introduction: Some studies have shown that a single session of resistance exercise can cause a lasting drop in blood pressure during recovery period after exercise, being a form of non-drug treatment of individuals with high blood pressure. Nevertheless, the literature is still controversial as to the prescription of resistance exercise for this purpose. Objective: To compare the behavior of blood pressure after 60 minutes of recovery from a resistance exercise session in series method with 40% and 80% of 1RM. Methods: Study participants were 12 normotensive men aged 24,9 ± 2,43; body mass 71,68 ± 5,18kg; height 173 ± 0,16 in; IMC 23,83 ± 1,60 kg/m2 and % fat of 16,84±2,99. The volunteers attended the laboratory for four trial sessions of weight training on alternated days: 1 – maximum load (1-RM) in six exercises (leg extension, bench press machine, leg curl and rowing machine), 2, 3 and 4 – in random order for the experimental sessions: 3 series of 8 repetitions of resistance exercise at 80% 1-RM session, 3 series of 16 repetitions of resistance exercise at 40% 1-RM session and a control (CONT) without performing the exercise. The variables measured at rest and after the experimental sessions, within 60 minutes of recovery were systolic blood pressure (SBP) and diastolic. Data were analyzed using descriptive statistics with mean and standard deviation. Two-way ANOVA for repeated measures was applied for comparison of results within and between experimental sessions with Post-hoc de Tukey test when necessary to detect possible differences (p < 0,05). The software Statistics for Windows 6.0 was employed. Results: According to the results, it was observed significant reduction in SBP, when comparing the final values of resistance exercise with a load of 80% of 1RM with SBP after 60 minutes of recovery. Regarding the double product, no significant change was observed. As for comparison between blood pressure and double product between exercise sessions at 40 and 80% of 1RM, there were no significant differences either. Conclusion: It is concluded that the hypotensive effect was not observed in any of the loads of resistance exercises, as well as no significant differences between systolic blood pressure, diastolic blood pressure and double product between the loads of 40 and 80% of 1RM.
Keywords: Hypotension; resistance exercise; double product